2013
DOI: 10.1002/rcm.6646
|View full text |Cite
|
Sign up to set email alerts
|

Strontium concentrations and isotope ratios in enamel of healthy and carious teeth in southern Shaanxi, China

Abstract: Sr plays a significant role in dental health, and there is a negative correlation between Sr and the occurrence of dental caries. The (87)Sr/(86)Sr ratio of teeth reflects the (87)Sr/(86)Sr ratio of the associated environment, and there is no significant relationship with the frequency of dental caries, age or sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Acid‐cleaned glass columns (4‐6 mm in diameter) loaded with Sr Spec resin was used to isolate Sr from potential interference elements. Although 8 mL of 3 mol/L HNO 3 has been shown to adequately isolate Sr from Rb during column separation, 8 mol/L HNO 3 was selected to avoid any elemental tailing and maximize the separation of other matrix elements . The method for Sr separation of dried wheat, soil and water samples is an optimized process (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Acid‐cleaned glass columns (4‐6 mm in diameter) loaded with Sr Spec resin was used to isolate Sr from potential interference elements. Although 8 mL of 3 mol/L HNO 3 has been shown to adequately isolate Sr from Rb during column separation, 8 mol/L HNO 3 was selected to avoid any elemental tailing and maximize the separation of other matrix elements . The method for Sr separation of dried wheat, soil and water samples is an optimized process (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Highly precise and accurate isotopic measurements are urgently required in multiple scientific areas such as the redefinition of the SI units, geochemistry, environment, geology, agriculture, nuclear science, archaeology, etc. Multi‐collector thermal ionization mass spectrometry (MC‐TIMS) is one of the state‐of‐the‐art techniques for high‐quality isotope analysis because its sources of uncertainty are relatively small and well understood .…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of dentin is largely influenced by the life-long deposition of elements, and related to gender and age (Kumagai et al 2012). As well as differences in Sr concentrations having been observed between the sexes (Li et al 2013), positive correlations have been observed between Sr concentrations and an individuals' age (Kumagai et al 2012).…”
Section: Discussionmentioning
confidence: 99%